Modulations in androgen and estrogen mediating genes and testicular response in male goldfish exposed to bisphenol A - Hatef, Azadeh; Zare, Ava; Alavi, Sayyed Mohammad Hadi; Habibi, Hamid R; Linhart, Otomar (Environmental toxicology and chemistry, 2012)
Adverse effects of bisphenol A (BPA) on reproductive physiology were studied in male goldfish (Carassius auratus) exposed to nominal environmentally relevant concentrations (0.2 and 20 µg/L) for up to 90 d. Transcriptions of various reproductive genes were measured in brain, liver, and testis to investigate the BPA modes of action. Volume, density, total number, motility, and velocity of sperm were measured to assess testicular function. At 0.2 µg/L, BPA reduced steroidogenetic acute regulatory protein and increased estrogen receptors (ERs) messenger RNA (mRNA) transcript (ERβ1 in liver and ERβ2 in testis) after 90 d. At 20 µg/L, BPA increased mRNA transcript of androgen receptor in testis, brain- and testis-specific aromatase, and vitellogenin in liver after 90, 30, 60, and 60 d, respectively. Transcripts of ERs mRNA were increased after 30 to 60 d at 20 µg/L BPA; increase in ERβ1 mRNA was observed in testis after 7 d. Total number, volume, and motility of sperm were decreased in males exposed to 0.2 and 20 µg/L BPA, whereas sperm density and velocity were only reduced at 20 µg/L BPA. The results support the hypothesis that BPA may exert both anti-androgenic and estrogenic effects, depending on concentration, leading to diminished sperm quality. The findings provide a framework for better understanding of the mechanisms mediating adverse reproductive actions of BPA observed in different parts of the world.
Keywords: testis; Estrogens; Phenols; Benzhydryl Compounds; zvířata; Testosterone; motilita spermií; messenger RNA; Testis; mužské pohlaví; benzhydrylové sloučeniny; aromatasa; karas zlatý; Sperm Motility; testosteron; Humans; androgenní receptory; estrogeny; Receptors, Androgen; receptory pro estrogeny; androgeny; RNA, Messenger; lidé; Vitellogenins; Receptors, Estrogen; Androgens; vitelogeniny; spermie; Aromatase; Animals; Organ Specificity; Spermatozoa; rozmnožování; Environmental Pollutants; Male; látky znečišťující životní prostředí; Goldfish; Reproduction; orgánová specificita; fenoly